Subsequent infection differentially affects the proteome of Caenorhabditis elegans by abrogating the intestinal cell proliferation. (January 2022) - Udayakumar, Prithika; Krishnaswamy, Balamurugan
Abstract: With a wide range of bacterial infections growing, it has become a big challenge to the research field to combat the newly emerging diseases. Immuno-compromised patients are vulnerable to opportunistic infections. P. mirabilis, an opportunistic pathogen infects the nematode when the immune system is compromised. In the present study, the C. elegans was pre-exposed to S. aureus for a short term, and then consecutively infected with P. mirabilis. The primary infection caused by S. aureus makes the immune system of C. elegans vulnerable making it easy for P. mirabilis to colonize efficiently during subsequent exposure, thereby stimulating the immune system of the nematode. In this study, the C. elegans exposed to the pathogens ( S. aureus 4 h/ P. mirabilis 40 h and S. aureus 8 h/ P. mirabilis 60 h time points) showed a substantial difference in the banding patterns of SDS-PAGE gel, when compared to their respective OP50 fed controls. 2-DE identified a total of 235 proteins from all the time points which had >2 fold regulation. The regulated protein spots were identified by MALDI-ToF/ToF analysis and one common protein CDC-25.1 was found to be regulated in all the comparative time points. CDC-25.1 seemed to down regulate during subsequent infection and up regulate in single infection. The transcriptomic regulation of cdc-25.1 also reflects the protein regulation. In addition to it, survival assay in cdc-25.1 mutant nematodes confirm the susceptibility of host during subsequent infection. Highlights: Subsequent infection of an opportunistic pathogen in C. elegans compromises its immune system. Proteomic modification in the cell division cycle (CDC25.1) plays a pivotal role in altering the immune response during the subsequent infection. The transcriptomic regulation of the corresponding genes also exhibits the similar expression patterns.